Social space of preschool institutions as a factor of gender equality - Miletić-Stepanović Vesna (Temida, 2021)
The subject of this paper is a sociological gender-sensitive analysis of the use-value of space in public preschool institutions (PPI), starting from the level of Serbian society, through Belgrade and Belgrade municipalities, down to the level of individual kindergartens. The objective of the research is to design the space of PPI facilities, which would provide the families and mothers with control over public space, and thus meet one of the preconditions for positive structural change - gender equality. The following parameters are used as indicators of the use-value of DPU space: the position of the preschool system in Serbia, coverage of children in the preschool system and preschool institutions by type of ownership, coverage of DPU children, insufficiency of DPU social space in Belgrade, compliance of available space in DPU municipalities Cukarica and Vozdovac with valid norms). Data sources: institutional data research (survey research “Spatial capacity of preschool institutions in Belgrade”, conducted at the Faculty of Geography, Department of Spatial Planning, on the subject of Social Development Planning, 2018-2019). The main results of this research confirm the presumed issue in this field, which causes the unequal gender power relations and various consequences which affect the position and quality of life of women-mothers and men. The preschool system in Serbia is in an unfavourable position due to the serious insufficiency of PPI facilities in Belgrade (out of a total of 124,846 preschool children, there is enough space for less than one half; the analysis of the existing PPI capacity shows that there are large differences in capacity at the municipal level, from about three quarters to about one quarter,) and at the level of Belgrade municipalities. The data available for the municipalities of Čukarica, Voždovac, Palilula, Zemun, Zvezdara, and Novi Beograd show that the same problem exists there as well, which can be solved by accepting the proposals for the required capacity of public kindergartens, which are given in this paper. The insufficient PPI capacity in the municipalities of Čukarica and Voždovac has been documented at the kindergarten level (a total of 55, 22 of which in the municipality of Čukarica, and 33 in the municipality of Voždovac.